Enhancing DevOps Practices in the IoT–Edge–Cloud Continuum: Architecture, Integration, and Software Orchestration Demonstrated in the COGNIFOG Framework - Petrakis, Kostas; Agorogiannis, Evangelos; Antonopoulos, Grigorios; Anagnostopoulos, Themistoklis; Grigoropoulos, Nasos; Veroni, Eleni; Berne, Alexandre; Azaiez, Selma; Benomar, Zakaria; Kakoulidis, Harry; Prasinos, Marios; Sotiriades, Philippos; et al. (Software, 2025)
This paper presents COGNIFOG, an innovative framework under development that is designed to leverage decentralized decision-making, machine learning, and distributed computing to enable autonomous operation, adaptability, and scalability across the IoT–edge–cloud continuum. The work emphasizes Continuous Integration/Continuous Deployment (CI/CD) practices, development, and versatile integration infrastructures. The described methodology ensures efficient, reliable, and seamless integration of the framework, offering valuable insights into integration design, data flow, and the incorporation of cutting-edge technologies. Through three real-world trials in smart cities, e-health, and smart manufacturing and the development of a comprehensive QuickStart Guide for deployment, this work highlights the efficiency and adaptability of the COGNIFOG platform, presenting a robust solution for addressing the complexities of next-generation computing environments.